Specific IgE and IgG4 Profiles of House Dust Mite Components in Allergen-Specific Immunotherapy - Yang, Lin; Yang, Yaqi; Xu, Qingxiu; Zhang, Wei; Jiang, Qing; Li, Wenjing; Wang, Yin; Ma, Dongxia; Lin, Xiaomin; Sun, Baoqing; Zhu, Rongfei (Frontiers in Immunology, 2022)
Background Allergen immunotherapy (AIT) can induce immune tolerance to allergens by activating multiple mechanisms, including promoting IgG4 synthesis and blunting IgE production. However, the longitudinal data of sIgE and sIgG4 to allergen components during AIT are limited. Objective We sought to investigate the persistence and evolution of sIgE and sIgG4 against house dust mite (HDM) components during AIT and explore their correlation with clinical responses. Methods Sixty allergic rhinitis (AR) with/without asthma patients receiving AIT for HDM were enrolled in AIT group. Thirty AR patients without receiving AIT served as control group. Blood samples were collected for sIgE, sIgG4 to HDM components (Derp 1, Derf 1, Derp 2, Derf 2, Derp 7, Derp 10, Derp 21 and Derp 23) assay at baseline, Month 6 and Month 18 of AIT. Combined symptom and medication scores (CSMS) were obtained accordingly. Results In the AIT group, sIgG4 to the HDM components of Derp 1, Derf 1, Derp 2 and Derf 2, Derp 21 significantly increased at Month 18 compared to the baseline (36.2 UA/mL vs 158.8 UA/mL, 46.4 UA/mL vs 94.6 UA/mL, 80.5 UA/mL vs 152.3 UA/mL, 78.3 UA/mL vs 205.1 UA/mL, 42.3 UA/mL vs 59.3 UA/mL, all p<0.05), sIgE to HDM components didn’t see differences at baseline and at Month 18 (all p>0.05).The numbers of positive HDM component sIgE and sIgG4 increased from 4.5 to 5 and 0 to 1.5 respectively (both p<0.05). However, the changes of sIgE, sIgG4, sIgE/sIgG4 ratio and the numbers of positive HDM components had no correlations with the improvement of CSMS after AIT (all ρ<0.3). For the control group, the sIgE and sIgG4 did not change significantly during the observational period (all p>0.05). Conclusion AIT can induce the production of sIgG4 to HDM components. However, the increased sIgG4 levels of HDM component do not correlate with the corresponding sIgE levels at baseline or with AIT response. sIgG4 to HDM components do not qualify as a biomarker to evaluate the efficacy of AIT.